A Comparative Study of Amoxicillin Sensitivity Against Escherichia coli Isolates Isolated from Urinary Tract Infections - Ali , Sameer Abdul ameer Abid; Aljeboury , Ghydaa H. (Iraqi Journal of Science, 2022)
The purpose of this study was to investigate the bacterial etiology of urinary tract infections microbiologic properties of Escherichia coli isolated from urinary tract infection patients against nine amoxicillin antibiotic. E.coli isolates were collected from patients samples suffering from urinary tract infection, based on biochemical tests of Epi 20 system .Nine Amoxicillin antibiotics were selected (some vials and other are capsules) which manufactured in different countries were bought from local pharmacies in Baghdad, for the purpose of knowing the inhibitory activity of these antibiotics on E.coli one of the main microorganisms to cause urinary tract infection, the antibiotics were prepared in a concentration of 100mg/ml and their activity was tested against the growth of the selected isolates and variations in the results were noted. Antimicrobial susceptibility was tested by the disk diffusion method. Results showed that. E. coli reveals variations in the susceptibility to amoxicillin.